2015
DOI: 10.1186/s40794-015-0008-3
|View full text |Cite
|
Sign up to set email alerts
|

Correlating quantitative real-time PCR to rapid diagnostic test and RNA transcript expression in isolated gametocytemia and asexual parasitemia of Plasmodium falciparum malaria

Abstract: BackgroundAt present, only microscopic examination of stained thick and thin blood smears for malaria can differentiate clinically relevant asexual parasitemia from clinically irrelevant isolated gametocytemia. Microscopy is time consuming, labour intensive, and requires significant technical expertise to perform. Simple and rapid tests that can distinguish asexual from isolated sexual parasitemia are needed.MethodsTo determine if parasitemia and cycle threshold (CT) values on Plasmodium genus and P. falciparu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…17 Several studies also showed that RDTs can detect HRP2 produced by circulating gametocytes. 18,19 If chronic submicroscopic infections or sexual stages of P. falciparum can produce enough HRP2 to be detected by some RDTs, then these tests may play an important role in surveillance of asymptomatic infections and in pre-elimination/elimination settings. However, the clinical relevance of these infections should also be considered, as symptoms such as fever may be falsely attributed to these infections, and other etiologies may be neglected.…”
mentioning
confidence: 99%
“…17 Several studies also showed that RDTs can detect HRP2 produced by circulating gametocytes. 18,19 If chronic submicroscopic infections or sexual stages of P. falciparum can produce enough HRP2 to be detected by some RDTs, then these tests may play an important role in surveillance of asymptomatic infections and in pre-elimination/elimination settings. However, the clinical relevance of these infections should also be considered, as symptoms such as fever may be falsely attributed to these infections, and other etiologies may be neglected.…”
mentioning
confidence: 99%